Pueraria mirifica can modulate the ovarian activity of crossbred-Thai native does - Satsook, Phubet; Rattanatabtimtong, Sukanya; Piasai, Lak; Towiboon, Patcharapa; Somgird, Chalermchart; Pinyopummin, Anuchai (The Thai Journal of Veterinary Medicine, 2022)
To evaluate the effect of P. mirifica supplementation on ovarian activity in crossbred Thai native does, a study was carried out for three consecutive estrus cycle periods: 1) D0-D21(pre-treatment), 2) D21-D42 (treatment) and 3) D42-D63 (post-treatment); D0, D21 and D42 were the days of expected estrus. P. mirifica was orally fed at 1000 mg/kg BW/d for 21 days in supplemented groups. Twenty-one does were equally divided into three groups: 1) CON – control, no supplementation and 2) supplemented groups included 2.1) FEC – start feeding at early-cycle (D21-D42), and 2.2) FMC – start feeding at mid-cycle (D32-D53). Estrus behavior was determined by observation, ovarian activity was monitored by transrectal ultrasonography and fecal progesterone concentration (FPC) was analyzed by EIA. The results showed that CON had lower (P<0.05) receptive behavior and shorter (P<0.05) estrous duration than those of FEC and FMC at treatment and post-treatment periods. FEC had a lesser number of developed follicles (P<0.05) and a greater number of undeveloped follicles than others at treatment period. FMC had a higher (P<0.05) number of undeveloped follicles at post-treatment period. Moreover, FEC and FMC had a higher (P<0.05) number of anovulatory follicles than that of CON, while only FMC had a lower (P<0.05) number of CLs along with a greater (P<0.05) number of early CL regression at the post-treatment period. FPC of FEC and FMC was lower than that of CON during administration. In conclusion, the P. mirifica dosage used in this study enhanced estrus behavior but suppressed ovarian activity in the consequent cycle when fed either at early or mid-cycle. Feeding over ovulation might have more adverse effects concerning CL function.